2021
DOI: 10.1111/1750-3841.15650
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of starches obtained from several native potato varieties grown in Cusco (Peru)

Abstract: Ten native potato varieties grown in Cusco (at 3,672 m above sea level) were used for starches extraction (at a pilot scale), and their physicochemical, functional, morphological, and structural characteristics were assessed. The content of protein, apparent amylose and phosphorus ranged from 0.1% to 0.44%, 23.42% to 35.5%, and 0.07 to 0.10%, respectively. Starch granules revealed smooth surface, with ellipsoidal and spherical shapes, particle size analysis exhibited bimodal or multimodal distribution, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
7
16
0
Order By: Relevance
“…Gelatinization of native starch began at 59.66 °C (To), reaching a maximum of 63.25°C, and was completed at 69.28 °C, with an enthalpy change of 12.61 J/g. These values coincide with a previous study on native starch (Martínez et al, 2021). On the other hand, a significant difference was found in the initial temperature (To), peak gelatinization temperature (Tp), and final temperature (Tf) between native starch (M0) and OSA starches (M1, M2, M3).…”
Section: Thermal Propertiessupporting
confidence: 91%
See 3 more Smart Citations
“…Gelatinization of native starch began at 59.66 °C (To), reaching a maximum of 63.25°C, and was completed at 69.28 °C, with an enthalpy change of 12.61 J/g. These values coincide with a previous study on native starch (Martínez et al, 2021). On the other hand, a significant difference was found in the initial temperature (To), peak gelatinization temperature (Tp), and final temperature (Tf) between native starch (M0) and OSA starches (M1, M2, M3).…”
Section: Thermal Propertiessupporting
confidence: 91%
“…1-C). Similarly, some studies on potato starches showed similar well-defined birefringence patterns in native granules (Martínez et al, 2019(Martínez et al, , 2021(Martínez et al, , 2022. OSA starch granules (M1-M3) showed that the shearassisted OSA treatment (Fig.…”
Section: Degree Of Substitutionsupporting
confidence: 56%
See 2 more Smart Citations
“…[23,24] The potato starch had a higher phosphorus content (0.07%) than the arracacha starch (0.03%). Similar phosphorous contents have been reported for potato [10,23,25,26] and arracacha starch. [27] The phosphorous content may affect some functional starch properties such as pasting and gel transparency.…”
Section: Amylose Phosphorous Content Solubility and Swelling Powersupporting
confidence: 85%